Perlindungan Hukum Bagi Korban Kekerasan dalam Hubungan Asmara Remaja Perspektif Sosiologi - Sabila, Amani; Amalia, Mia; Mulyana, Aji (Journal of Contemporary Law Studies, 2024)
This research discusses legal protection for victims of violence in teenage romantic relationships from a sociological perspective, with the aim of providing a comprehensive picture of legal efforts to protect victims while highlighting social aspects that are relevant in the preparation of protection policies. Using qualitative methods, data were collected through in-depth interviews, document studies, and participatory observation. Data analysis techniques were thematic, identifying social and legal patterns that influence the dynamics of violence in teenage romantic relationships. The results showed that violence in teenage romantic relationships is often influenced by social factors such as cultural norms, family parenting, and media influence. On the other hand, existing legal protection is still not optimal in reaching the specific needs of adolescents as victims. This study recommends a more inclusive policy by paying attention to educational aspects, strengthening public awareness, and integrating sociological approaches in the legal system to ensure more effective protection.